Convivendo com a Aids e seu tratamento : experiência de portadores e familiares - Silva, Ana Lúcia Cardoso Nogueira da (2007)
The objective of this study was to understand the aspects that influence patients with Aids and their relatives whether or not to take part in antiretroviral therapy. It is an exploratorydescriptive study, of a qualitative nature, undertaken with 10 bearers of HIV/Aids, monitored at the Specialized Care Service (SCS) for Aids in Campo Mourão, Paraná State, and their respective family caretakers. Data was collected in two stages, during the months of June 2006 and April 2007, using SCS document sources to describe the users, and two interview scripts - one for people living with Aids and another for their caretakers. The interviews, of the semi-structured type, were conducted individually with the patient, and later with the relative, in the home, according to the availability of both subjects and researchers. They lasted on average 40 minutes, and were recorded after consent was given. When selecting subjects, the fact that they attended the data collection stages along with their family caretaker was taken in consideration. The Thematic Analysis, according to (MINAYO, 2004) was used as reference for data analysis. The development of the study followed the ethical precepts underlined by Resolution n° 196/96, and the project was approved by the Committee of Ethics in Research with human beings of the State University of Maringá (decision 208/2006). Seven men and three women took part in the study, with ages between 26 and 60; seven were married, two were in stable unions and one was divorced. In regard to education, six of them had completed middle school and four had graduated from high school. As for the caretakers, nine were companions and one was a sister of the subject; they were between 25 and 60 years old, had little formal education and none of them were officially employed, although two of them worked as cleaning ladies, but without formal work registration. The analysis of the interviews allowed the identification of two broad categories: a) The impact of the discovery of positive status for the bearer and his/her family, showing that in spite of the current strategy by the National Program for STDs/Aids of valuing prevention, out of the 10 interviewees, seven found out their positive HIV status after the occurrence of opportunistic diseases, two women during prenatal care and only one at the Center for Testing and Counseling. This category is comprised of the following sub-categories: Being diagnosed as an HIV/Aids bearer - an unexpected fatality; The calm after the storm: Feelings upon the discovery of the positive diagnosis and the challenges of living with Aids, which evidence the influence of the condition of being a bearer of HIV/Aids in their conceptions of health and the changes in the bearer's daily life as an adaptation to the diagnosis of HIV; b) Participation and non-participation in antiretroviral therapy: two faces of the same existence, which shows the bearer living with HIV/Aids in his/her daily life, with emotional, financial, physical and even religious difficulties, factors that interfere in the process of participation in ARV therapy, and that gave origin to the following sub-categories: Facilitating and dissuading factors for participation; The patient creating strategies to facilitate participation; The importance of religiosity and a social network as conditions for participation. In views of the results and having worked for 10 years in the Specialized Service Clinic, I can say that even when rendering humanized care along with a multidisciplinary team, I never expected to find such evident results of non-participation, with important flaws between the care rendered in the form of instructions and the care that is learned and put in practice by patients. The results demonstrate that the human being should be instructed within his/her bio-psycho-socialspiritual context, in a continuous learning process between the caretaker and person being cared for.